Hablando de Luis Barragán - Paz, Octavio
Artículo escrito con motivo de la entrega del Pritzker al arquitecto Luis Barragá, en 1980.
Keywords: BARRAGAN, LUIS; PREMIOS PRITZKER; ARQUITECTOS; TRAYECTORIA PROFESIONAL